Interventional Oncology Service Development - Mouli, Samdeep; Baker, Jennifer C.; Brown, Daniel B. (Seminars in Interventional Radiology, 2017)
Interventional oncology is rapidly expanding its suite of oncologic therapies, providing unique proven therapeutic benefits. To grow a practice alongside other oncology specialties, knowledge of cancer fundamentals is required. Areas of interest include methods to assess disease stage, treatment toxicity, and response. Additionally, techniques to leverage opportunities and resources available at one's institution toward practice development and efficiency will be reviewed.
Keywords: interventional radiology; chemoembolization; radioembolization; radiofrequency ablation; practice development